Quantum Key Distribution for Secure Electronic Voting Systems - Vasilis Antoniou; Maria Nikolaou; Tigran Sargsyan (Journal of Tecnologia Quantica, 2025)
The background of this research focuses on the security challenges faced by electronic voting (e-voting) systems that are vulnerable to the threat of eavesdropping and data manipulation. As the use of digital technology in elections increases, innovative solutions are needed to ensure the integrity and confidentiality of voters' votes. This study aims to explore the application of Quantum Key Distribution (QKD) in a safe and reliable e-voting system. The method used is a case study of the implementation of QKD in various e-voting trials in several countries, with an analysis of the test results of the success rate, security, and speed of data transmission. The results show that the application of QKD in the e-voting system is able to provide a security level of up to 99%, even with a decrease in data transmission speed compared to conventional systems. The resulting security is much higher, overcoming the potential for eavesdropping and data forgery attacks. The conclusion of this study is that QKD can be an effective solution to improve security in e-voting systems, although transmission speed challenges need to be improved. Further research is needed to optimize this technology so that it can be applied at scale with better efficiency.